Infusions and decoctions of dehydrated fruits of Actinidia arguta and Actinidia deliciosa: Bioactivity, radical scavenging activity and effects on cells viability - Silva, A.M. (2020)
Actinidia deliciosa and A. arguta fruits (kiwifruit and kiwiberry, respectively) are an excellent source of bioactive compounds. The aim of this paper is to valorize the fruits that are not commercialized (e.g. due to inadequate size or physical damage) in infusions and decoctions. The antioxidant activity, the scavenging activity against reactive species, the phenolic profile and the intestinal effects of infusions and decoctions of dehydrated fruits were evaluated and compared. Decoctions presented the highest antioxidant activity and a good ability to capture HOCl and NO. The phenolic composition of A. arguta present quinic acid, cis-caftaric acid and its derivatives, caffeoyl hexoside, luteolin glucuronide, quercetin derivatives and myristin, while A. deliciosa extracts were characterized by the presence of quinic acid, caffeic acid and its derivatives and caffeoyl hexoside. No adverse effects were observed on Caco-2 and HT29-MTX cells. Kiwiberry decoctions showed to be the best option to keep the fruits benefits.